OVO Payment on Grab App: A Fiqh Muammalah Perspective among Muslim Student - Falira Alifia Zahra; Hubbul Wathan; Rizal Agus; Supaino Supaino; Anriza Witi Nasution (Studia Economica : Jurnal Ekonomi Islam, 2025)
The purpose of this study is to determine the mechanism of OVO payment system discounts on the Grab application and to determine the Fikih Muamalah analysis of the mechanism of OVO payment system discounts on the Grab application. The subjects of this study are Muslim students at the Medan State Polytechnic. This study uses qualitative data. The data sources used are primary and secondary data. Data collection techniques include interviews, documentation, and observation. Validation tests are conducted using interview data and triangulation techniques. The results of the study show that the OVO payment method discount scheme on the Grab application has been structured and transparently organized, covering terms and conditions, promotional periods, quotas, and the rights and obligations of all parties. In principle, this system has fulfilled the principles of fairness, certainty, and avoidance of elements of gharar, dhulm, and israf. This practice is in line with the spirit of MUI DSN Fatwa No. 116/DSN MUI/IX/2017, which requires protection for users, merchants, and drivers in digital transactions. Second, OVO's discount practice can be justified through two sharia contracts: Wadi'ah Contract: user balances are stored as deposits that can be withdrawn at any time, without being used by the issuer except with the permission of the holder, and Qardh Contract: if the issuer uses the balance (for example, for investment), then the discount serves as a voluntary reward that does not contain usury